Urban energy transition in a gaming context: The role of children. (December 2021) - Hettinga, Sanne; Boter, Jaap; Dias, Eduardo; Fruijtier, Steven; de Vogel, Brian; Scholten, Henk
Highlights: Children are often overlooked as stakeholder in spatial energy transition planning. We present a game-based SDSS with appropriate context to collect their input. A pilot shows it helps children to provide diverse and viable transition plans. But boundaries and scale of study area should match children's familiarity. Abstract: The transition to sustainable energy in a neighbourhood is not a trivial process and current efforts attempt to garner support and engagement from local stakeholders through public participation processes. This paper presents a game-based decision support system specifically designed to include a relevant (yet often overlooked) group of stakeholders: the children of an area. Combining the principles of public participation and Geodesign, it supports children to learn about and plan renewable energy technologies in their neighbourhood. A pilot in the South-East district of Amsterdam, the Netherlands, shows that this decision support system can collect relevant input from children. Their plans display a diversity in renewable energy technologies applied and building improvements. Furthermore, an impact analysis demonstrates that the children have learned what buildings were suitable for specific technologies. Maps of the results suggest that selecting an appropriate study location for the children is important, to allow planning at a scale proportional to the local knowledge and planning time. The results provide insights into what type of solutions are preferred, the diversity of the solutions and most important, the solutions are spatially explicit about the participants preferences. This demonstrates that such methods are effective in reaching out to and surveying the preferences of this difficult to reach stakeholder group.